The use of essential drugs : third report of the WHO Expert Committee, meeting held in Geneva from 30 November to 4 December 1987 - WHO Expert Committee on the Use of Essential Drugs; World Health Organization (Geneva : World Health Organization, 1988)
Presents and explains the fifth WHO model list of essential drugs, incorporating revisions agreed upon by a 19-member committee of experts. The report also provides updated information on several other components of national drug policy necessary to assure that essential drugs, corresponding to priority health needs, are available at all times in adequate amounts and in the proper dosage forms. Organized according to therapeutic group, the list includes information on route of administration, dosage forms, and strengths for each of 277 drugs included in the main list and in a complementary list. The complementary list includes drugs for use when drugs in the main list cannot be made available or are known to be ineffective or inappropriate for a given individual, are needed for the treatment of rare disorders or in exceptional circumstances, or should be considered for use only when appropriate facilities for drug surveillance are available
1. Introduction -- 2. Guidelines for establishing a national programme for essential drugs -- 3. Criteria for the selection of essential drugs -- 4. Guidelines for the selection of pharmaceutical dosage forms -- 5. Applications of the essential-drugs concept -- 6. Essential drugs and primary health care -- 7. Quality assurance -- 8. Drug utilization surveys -- 9. Research and development -- 10. Drug information and education activities -- 11. Updating of lists of essential drugs -- 12. Model list of essential drugs -- 13. Changes made in revising the model list -- 14. Glossary of terms used in the report -- 15. Alphabetical list of essential drugs
Keywords: Drugs, Essential; Pharmacology, Toxicology and Clinical Technology